¿Puede una política fiscal contractiva ser expansiva? La efectividad de la política fiscal y la sostenibilidad de la deuda pública - Mendoza, Waldo (2007)
This paper presents a Keynesian effective demand model that reproduces expansive or contractive effects of an expansionary fiscal policy as a function of the initial conditions of the public finances.In an economy with fiscal slack, when observed primary surplus is above the optimal fiscal surplus level, expansive fiscal policy raises the level of economic activity.However, when there is no fiscal slackness, when the observed surplus is below the optimal surplus, a fiscal expansion may contract the level of economic activity.The outcome has implications for the debate about whether fiscal policy should be countercyclical or not. In the aforementioned scenery the countercyclical policy is appropriate only when there is fiscal slackness, but it is counterproductive, wouldaggravate the recession instead of ameliorating it, whenever at the initial point the observed fiscal surplus is below the optimal surplus level.